A three-phase state estimation algorithm for unbalanced distribution networks - Yap, Jian Liang. (2013)
This project aims to develop a three-phase State Estimation (SE) algorithm that considers unbalanced characteristics of specific distribution networks by incorporating KVL loop equations.